Efficient Removal of Multiple Heavy Metals from Simulated Wastewater using Combined Carbonized Palm Shell and Rice Husk Adsorbents in Multi-Column System - Alsadek Ali Alguail; Ali H. Al-Eggiely; Ali S. Ebshish (African Journal of Advanced Pure and Applied Sciences, 2024)
This research study amid to develop a hybrid-modified adsorbent from carbonized palm shell and rice husk to remove heavy metal components from simulated wastewater using multi-bed column adsorption. Physical treatment for the adsorbents was done before conducting the experiments. Removal of 13 heavy metal components were investigated in this work and the adsorption performance was compared to that of single bed column adsorption. Six types of adsorbents, including one pure blended rice husk adsorbent, one pure carbonized palm kernel shell adsorbent, and four hybrid adsorbents with different mixing ratios (20%, 40%, 60%, and 80%wt) of blended rice husk and carbonized palm kernel shell were used in this study. Surface morphology analysis was conducted using Field Emission Scanning Electron Microscope (FESEM) for each adsorbent, and adsorption performance was evaluated by area under the graph analysis. The results showed that cadmium, copper, vanadium, antimony, and zinc were effectively adsorbed by the hybrid adsorbent compared to single adsorbents. The adsorption capacity was increased in multi-layer bed adsorption, and the hybrid adsorbent with multi-bed layer column performed better than single-layer bed column. In conclusion, a hybrid adsorbent of mixing of rice husk and carbonized palm shell and applying multi-bed layer column adsorption contributed to enhanced adsorption performance of removing multiple heavy metals from wastewater.